Efficacy and Safety of PARP Inhibitors in Advanced or Metastatic Triple-Negative Breast Cancer: A Systematic Review and Meta-Analysis - Liu, Xu; Wu, Kan; Zheng, Dan; Luo, Chuanxu; Fan, Yu; Zhong, Xiaorong; Zheng, Hong (Frontiers in Oncology, 2021)
Purpose: Poly (ADP-ribose) polymerase (PARP) inhibitors have shown promising results in metastatic triple-negative breast cancers (TNBC). We therefore performed a systematic review and meta-analysis to evaluate the efficacy and safety of this drug in patients with advanced or metastatic TNBC. Methods: A systematic literature search of PubMed, Embase, Scopus, Web of Science and Cochrane Central Register of Controlled Trials for synonyms of ‘PARP inhibitors’ and ‘breast cancer’ was carried out. All published phase II/III clinical studies of PARP inhibitors in advanced/metastatic TNBC patients were screened. Data were extracted independently by two authors and analyzed using Review Manager software version 5.3. End points include overall response rate (ORR), progression-free survival (PFS) and adverse events. Results: Ten clinical trials were identified, with a total of 1495 patients included. Pooled analyses showed that PARP inhibitors could provide a significant improvement of ORR (risk ratio [RR]=2.00, 95% confidence interval [CI]: 1.14–3.50, p=0.02) and PFS (hazard ratio [HR]=0.68, 95 %Cl: 0.59-0.77, p<0.0001) compared to chemotherapy in the whole population. In subgroup analysis, germline/somatic BRCA mutated patients had a higher objective response to PARP inhibitor, with a RR of 2.85 (95%CI: 1.34–6.06, p=0.007) compared to BRCA wild-type patients. However, no significant difference in ORR was observed between the homologous recombination deficiency (HRD) positive and non-HRD subgroups (RR=1.82, 95%CI: 0.81–4.08, p=0.14). Hematologic toxicity is a common adverse event of PARP inhibitors. Conclusions: PARP inhibitors are effective options for the treatment of advanced or metastatic TNBC patients. Compared with BRCA wild-type patients, patients with germline/somatic BRCA mutations could benefit more from PARP inhibitors. In clinical applications, hematological toxicity associated with PARP inhibitors should be monitored regularly.